2020
DOI: 10.1001/jama.2020.11370
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Built Environment, Neighborhood Socioeconomic Status, and SARS-CoV-2 Infection Among Pregnant Women in New York City

Abstract: Agency. Advisory memorandum on identification of essential critical infrastructure workers during COVID-19 response. April 17, 2020. https://www. cisa.gov/sites/default/files/publications/Version_3.0_CISA_Guidance_on_ Essential_Critical_Infrastructure_Workers_1.pdf 5. LMI Institute. SOC codes for CISA critical infrastructure workers. Rev 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
152
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(164 citation statements)
references
References 3 publications
10
152
0
2
Order By: Relevance
“…Further, we were able to refine previous associations between infection and hospitalization rates with area-level household crowding. In fact, this association is consistent with smaller studies 33,34 and may partially explain racial disparities seen in aggregated county-level data. 19 For example, approximately one-fifth of US residential units are unsuitable for home quarantine based on the number of rooms available per individual, with racial and ethnic minorities overrepresented among these households.…”
Section: Baseline Characteristicssupporting
confidence: 88%
“…Further, we were able to refine previous associations between infection and hospitalization rates with area-level household crowding. In fact, this association is consistent with smaller studies 33,34 and may partially explain racial disparities seen in aggregated county-level data. 19 For example, approximately one-fifth of US residential units are unsuitable for home quarantine based on the number of rooms available per individual, with racial and ethnic minorities overrepresented among these households.…”
Section: Baseline Characteristicssupporting
confidence: 88%
“…While there are many unanswered questions regarding the clinical course of COVID-19, we know that older adults, African-Americans, and those with comorbidities such as hypertension, chronic lung disease, and diabetes are disproportionately affected. 2,3 Though the mechanisms for these differences have not been fully elucidated, there is evidence that neighborhood level structural factors such as crowding may contribute, 4 and concern that already existing inequities in healthcare access and outcomes may be worsened by the pandemic. 5 From an epidemiological perspective, whether or not pregnant women experience more severe disease is challenging to answer.…”
Section: Introductionmentioning
confidence: 99%
“…The Effect of interaction within a population community on the growth of virus infected number is demonstrated in Fig 7. The output from the model suggest that minimum the interaction, earlier the curve attens. The results from Shamam model [17] based on metapopulational SIER model indicates the same trend. The authors concluded that individual living in highly populated neighborhood was infected more.…”
Section: Effect Of Interactionmentioning
confidence: 54%